Curdlan as a new depressant of hematite for quartz-hematite reverse flotation separation. (July 2022) - Han, Wenjie; Zhu, Yimin; Ge, Wencheng; Liu, Jie; Li, Yanjun
Graphical abstract: Highlights: Curdlan was a clean and efficient polysaccharide depressant of hematite. Curdlan could selectively depress hematite and had a weak dispersion effect on quartz, which made it more selective. Curdlan was selectively adsorbed on hematite through chemical bonds between hydroxyl and iron atoms. Abstract: In this study, the quartz-hematite reverse flotation separation was realized by using curdlan to selectively depress hematite. The behavior of curdlan on quartz-hematite reverse flotation separation was researched by micro-flotation tests. And, its depression mechanism on the hematite was researched with zeta-potential measurements, turbidity measurements, FT-IR and XPS analyses. It can be seen from the results of micro-flotation tests that curdlan could reduce the floatability of hematite without affecting quartz. The grade of iron concentrate improved to 65.03% (Recovery was 90.03%), at pH 11.5 and concentration of curdlan 20 mg/L. Turbidity tests showed that curdlan-treated hematite flocculated in the pulp, while curdlan-treated quartz dispersed in the pulp. This was due to the adsorption of curdlan on hematite surface (i.e., the bridging of reagents) overcame the electrostatic repulsion between hematite particles. Zeta potential results showed that curdlan was adsorbed strongly non-electrostatically to the surface of hematite, but weakly adsorbed to quartz. FT-IR analyses showed that curdlan adsorbed on the hematite surface first, which hindered the subsequent adsorption of NaOl and Ca 2+ on the surface of hematite. However, no characteristic peaks of curdlan were found on the surface of the quartz, and the quartz treated by curdlan and Ca 2+ could still adsorb NaOl. XPS analyses demonstrated further that curdlan was chemically bonded to Fe sites on the hematite surface through its hydroxyl group.